Compound, acrylic resin, planarization layer composition and application
By using a planarized layer composition prepared with a specific composition acrylic resin material, the problems of insufficient adhesion, excessive dielectric constant and poor tolerance of existing materials are solved, and the higher display effect and manufacturing efficiency of TFT-LCD are achieved.
Patent Information
- Application Number
- CN202411704355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing planarized layer materials have problems such as insufficient adhesion, excessive dielectric constant and poor tolerance in the TFT-LCD manufacturing process, resulting in reduced display quality and low manufacturing efficiency.
A new acrylic resin material is used, which consists of specific compounds, acrylic compounds, acrylate compounds, styrene compounds and epoxy compounds, and is prepared by radical polymerization to form a planarized layer composition with excellent surface coating properties, density and anti-solvent properties.
It significantly improves adhesion to the chromoresis layer, reduces the dielectric constant, and enhances the tolerance to organic solvents, thereby optimizing the display effect and manufacturing efficiency of TFT-LCD, and improving the reliability and durability of the product.
Smart Images

Figure CN119613439A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a compound, an acrylic resin, a planarization layer composition and applications. Background Art
[0002] With the rapid development of science and technology, thin-film transistor liquid crystal display (TFT-LCD), as a core component of modern display technology, has been widely used in various electronic products such as smart phones, tablet computers, TVs and computer monitors. Its excellent display performance and efficient manufacturing process make it the mainstream choice in the market. However, in the manufacturing process of TFT-LCD, the design and production of color film substrate (CF) is one of the key links, which is directly related to the quality of the final display effect. The color film substrate achieves full-color display through precisely arranged three primary colors (red, green, and blue) pixels, but two major problems are inevitably encountered in this process: the display quality is reduced due to sub-pixel step difference and angular step difference. The sub-pixel step difference mainly comes from the slight difference in the thickness of the liquid crystal box between different pixels, which affects the transmittance of light and thus affects the brightness uniformity; while the angular step difference may cause the disorder of the arrangement of liquid crystal molecules, causing light leakage, which seriously affects the display effect.
[0003] In order to overcome the above problems, the traditional practice is to apply a flattening layer (OC) after the color resist process is completed, aiming to eliminate or reduce the adverse effects of sub-pixel step difference and angular step difference through its excellent flattening ability. At the same time, since the color resist layer often contains metal ion components, if these components are directly exposed to the liquid crystal layer, they may cause poor display problems such as afterimages. Therefore, as a barrier, the OC layer can effectively prevent metal ions from diffusing into the liquid crystal layer with its high electrical resistance, thereby protecting the purity and stability of the liquid crystal layer. In addition, as a key structure for maintaining the gap between the liquid crystal cells, the high uniformity of the columnar spacer (PS) is crucial to ensuring the display effect. The flattening effect of the OC layer not only optimizes the surface morphology of the color filter substrate, but also provides a good foundation for the uniform distribution of PS, which helps to achieve more precise pixel control and more stable display effects. However, the flattening layer materials currently widely used in the market still have deficiencies in many aspects of performance. For example, its adhesion is not enough to ensure a close bond with the color resist layer, which may lead to interlayer peeling; a too high dielectric constant may interfere with the normal operation of the TFT device; at the same time, in subsequent processes, its tolerance to organic solvents (such as NMP and PGMEA) is insufficient, and it is easily damaged during cleaning or processing, affecting the product yield and reliability. Summary of the invention
[0004] In order to overcome the above technical problems, the present invention aims to provide a planarization layer material and a preparation method thereof. The material not only has excellent surface coating performance, compactness after heat drying, and good anti-solvent dissolution performance, but also can significantly improve the adhesion with the color resist layer and reduce the dielectric constant, thereby comprehensively optimizing the display effect and manufacturing efficiency of TFT-LCD.
[0005] In one aspect, the present invention relates to a compound having a structure as shown in formula (I):
[0006] On the other hand, the present invention relates to an acrylic resin, wherein the constituent monomers of the acrylic resin include a compound represented by formula (I), an acrylic compound, an acrylic ester compound, a styrene compound, and an epoxy compound.
[0007] Generally, in the planarization layer material, the compound of formula (I) is added in an amount of 5% to 15% of the total amount of the resin monomers, in terms of mass percentage.
[0008] Illustratively, in the acrylic resin provided by the present invention, the acrylic compound is selected from at least one of acrylic acid and methacrylic acid; The acrylic acid ester compound is selected from at least one of methyl methacrylate, methacrylate, butyl methacrylate, tert-butyl methacrylate, lauryl methacrylate, decyl methacrylate, isobornyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, hydroxyethyl methacrylate, adamantyl methacrylate, dicyclopentyl methacrylate, and perfluorobutyl methacrylate; The styrene compound is selected from at least one of styrene, α-methylstyrene, 4-hydroxystyrene, 4-tert-butoxystyrene, 4-boc-styrene, p-divinylbenzene, and 4-isopropenylphenol; The epoxy compound is selected from at least one of glycidyl methacrylate, tetrahydrofurfuryl methacrylate, and 3,4-epoxycyclohexyl methacrylate.
[0009] Illustratively, in the acrylic resin provided by the present invention, the acrylic resin is formed by polymerizing the constituent monomers in a first solvent; The first solvent is selected from at least one of diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, methyl lactate, ethyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
[0010] Furthermore, in the acrylic resin provided by the present invention, the molecular weight of the acrylic resin is 3000-10000 Mw, the PDI is 2.0-3.0, and the solid content is 25%-35%.
[0011] In another aspect, the present invention relates to a planarization layer composition, comprising the acrylic resin.
[0012] The acrylic resin in the planarization layer composition is generally prepared by free radical polymerization.
[0013] Furthermore, in the planarization layer composition provided by the present invention, the acrylic resin accounts for 1-30 wt % of the planarization layer composition.
[0014] Furthermore, in the planarization layer composition provided by the present invention, the planarization layer composition is composed of the following components in parts by mass: 10 to 300 parts of the acrylic resin; 10~300 parts of active diluent; 1~10 parts of photoinitiator and / or thermal initiator; 5~20 parts of coupling agent; 1~10 parts of surfactant; 1~10 parts of antioxidant; 10-80 parts of the second solvent.
[0015] Reactive diluents are generally small molecule monomers or polymers, which can enhance the degree of polymerization of the composition through light or heat, and improve the physical and chemical properties of the composition such as cross-linking degree, viscosity, leveling performance, adhesion, film surface flatness, etc.; antioxidants are generally hindered phenol compounds; coupling agents are generally multifunctional compounds.
[0016] Illustratively, in the planarization layer composition provided by the present invention, the reactive diluent is selected from at least one of glycidyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, hydroxyethyl methacrylate, and styrene; The photoinitiator is selected from at least one of Irgacure® OXE01, Irgacure® OXE02, IRGACURE® 819, Irgacure® 290, benzophenone, diphenylacetophenone, and 2,2-dimethoxy-phenylacetophenone; The thermal initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; The coupling agent is selected from at least one of divinylbenzene, 3,4-epoxycyclohexyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, KH-560, and KH-570; The surfactant is selected from at least one of TritonX-100, OP-10, polyoxyethylene sorbitan fatty acid ester, sulfobetaine, lecithin, KP-341, KP-420, KP-611, BYK-301, BYK-310, and BYK-3450; The antioxidant is selected from at least one of antioxidant 330, antioxidant 1010, antioxidant 1076, and antioxidant 3114; The second solvent is selected from at least one of diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, methyl lactate, ethyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
[0017] The compound, acrylic resin, and planarization layer composition provided by the present invention have good flatness, adhesion, low dielectric properties, and good tolerance. Therefore, the present invention further requests protection for the use of the compound, the acrylic resin, or the planarization layer composition in a thin film transistor liquid crystal display, wherein the thin film transistor liquid crystal display is coated with a planarization layer to improve at least one of the flatness, adhesion, dielectric properties, and tolerance.
[0018] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: The present invention provides a compound, and an acrylic resin containing the compound has good flatness, adhesion, low dielectric properties and good tolerance when used for the preparation of a planarization layer. The present invention solves the technical problems of insufficient adhesion, dielectric constant and tolerance of planarization layer materials. By optimizing the surface coating performance of the material and the compactness after heat drying, the present invention effectively eliminates the display quality problems caused by sub-pixel step difference and angular step difference in the manufacturing process of TFT-LCD, such as uneven brightness and light leakage, thereby significantly improving the display effect of the final product, making the color more vivid and the image clearer. The planarization layer material of the present invention exhibits excellent adhesion with the color resist layer, effectively avoids the problem of interlayer peeling, and improves the reliability and durability of the product. At the same time, the material shows good tolerance to a variety of organic solvents such as IPA, NMP, TMAH and DIW, is not easily damaged during cleaning or processing, and ensures the yield rate and product quality stability in the production process. The low dielectric constant characteristics of the material provided by the present invention help to reduce delays and energy losses in the signal transmission process, improve the electrical properties of the TFT device, and improve the response speed and efficiency of the overall display system. The planarization layer material of the present invention has a low density, which helps to reduce the weight of the overall device. At the same time, its physical properties such as high hardness, low water absorption and low film surface roughness provide better conditions for subsequent pattern production and photolithography processes, simplify the manufacturing process, and improve production efficiency and yield. The present invention has significant advantages in improving the display effect of TFT-LCD, enhancing material performance, optimizing the manufacturing process, and improving product reliability and durability, and has broad application prospects and important market value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 Schematic diagram of the structure of the planarization layer in the color filter substrate, where 1 represents the glass substrate, 2 represents the black matrix, 3 represents the red pixel, 4 represents the green pixel, 5 represents the blue pixel, and 6 represents the planarization layer.
[0021] Figure 2 This is the H NMR spectrum of the intermediate methacrylate prepared in Example 1.
[0022] Figure 3 This is the H NMR spectrum of the compound of formula (I) prepared in Example 1.
[0023] Figure 4 This is the GPC chart of acrylic resin R-1 prepared in Example 2.
[0024] Figure 5 This is the GPC chart of acrylic resin R-2 prepared in Example 2.
[0025] Figure 6 This is the GPC chart of acrylic resin R-3 prepared in Example 2.
[0026] Figure 7 This is the GPC chart of acrylic resin R-4 obtained in Example 2.
[0027] Figure 8 The GPC diagram of acrylic resin R-5 obtained in the comparative example is Fig. 9 This is a test chart of film adhesion (cross-hatch method).
[0028] Fig.10 This is the outgas (TGA) diagram. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials are available on the market unless otherwise specified, and the % in the following examples are all mass percentages unless otherwise specified.
[0030] Example 1 This example provides the preparation process and characterization of the compound represented by formula (I).
[0031] Under nitrogen protection, 1L of dichloromethane and 424g of 4,4'-dihydroxystilbene were added to a 5L three-necked flask, and the temperature was lowered to 0°C while stirring. 760g of m-chloroperbenzoic acid and 1.5L of dichloromethane solution were added dropwise to the reaction system. The temperature was controlled at -5°C to 5°C during the addition process. After the addition was completed, TLC monitored the raw materials until the raw materials disappeared. After the reaction was completed, the reaction solution was poured into saturated brine while stirring. After the organic phase was extracted, it was washed with saturated brine until neutral, concentrated and dried to obtain 460g of crude intermediate epoxy compound.
[0032] Under nitrogen protection, 2L of dichloromethane, 460g of the above-mentioned crude epoxy intermediate, and 202g of triethylamine were added to a 5L three-necked flask, and the temperature was lowered to 0°C while stirring. 187.2g of methacryloyl chloride was added dropwise to the reaction, and the temperature was controlled at -5°C to 5°C during the addition. After the addition was completed, TLC monitored the raw materials until the raw materials disappeared. After the reaction was completed, the generated solid was filtered, and the filtrate was poured into saturated brine with stirring. After the organic phase was extracted, it was washed with saturated brine until neutral, concentrated and dried, and column chromatography (developing solvent n-hexane: dichloromethane = 2:8, v / v) was performed, and recrystallization was performed to obtain 248g of methacrylate intermediate.
[0033] Under nitrogen protection, 1L of dichloromethane, 102g of methacrylate intermediate, and 37.6g of triethylamine were added to a 3L three-necked flask, and 52.2g of trimethoxychlorosilane was added dropwise to the reaction. The temperature was controlled at 20°C to 30°C during the addition. After the addition was completed, TLC was used to monitor the raw materials until the raw materials disappeared. After the reaction was completed, the filtrate was poured into saturated brine with stirring. After the organic phase was extracted, it was washed with saturated brine until neutral, concentrated and dried, and column chromatography (developing solvent n-hexane: dichloromethane = 5:3, v / v) was performed, and recrystallization was performed to obtain 71g of compound of formula (I).
[0034] Figure 2 The H NMR spectrum of the intermediate methacrylate for preparing the compound of formula (I) shows that the two multiple peaks in the chemical shift of 5.55-6.05 in the spectrum are consistent with the chemical shift of the two hydrogens on the epoxypropyl group, indicating that epoxy has been formed; the hydroxyl hydrogen integral is 1, indicating that one of the two hydroxyl groups in the raw material forms an ester, and the compound is the target compound; Figure 3 To prepare the H NMR spectrum of the compound of formula (I), combined with Figure 2 In the hydrogen spectrum of the intermediate, the hydroxyl hydrogen signal disappeared, and three methoxy hydrogen signals appeared in the spectrum, indicating that the compound was the target compound of formula (I).
[0035] Example 2 This example provides the synthesis of acrylic resin R-1.
[0036] Under nitrogen protection, 125 g of the compound represented by formula (I), 137.5 g of methacrylic acid, 300 g of glycidyl methacrylate, 210 g of 3,4-epoxycyclohexyl methacrylate, 155 g of styrene, 125 g of tert-butyl methacrylate, 42.5 g of α-methylstyrene dimer, 120 g of azobisisoheptanenitrile, and 2850 g of diethylene glycol methyl ethyl ether were added to a 5 L three-necked flask, and the temperature was raised to 70° C. with stirring, and the reaction was carried out for 4 h. The temperature was then lowered to room temperature to obtain an acrylic resin with Mw=7366, PDI=2.0, solid content of 26.95%, and viscosity of 18.59 cP.
[0037] Example 3 This example provides a synthesis of acrylic resin R-2 Under nitrogen protection, 145 g of the compound represented by formula (I), 137.5 g of acrylic acid, 359 g of tetrahydrofurfuryl methacrylate, 200 g of 3,4-epoxycyclohexyl methacrylate, 145 g of styrene, 88 g of methyl methacrylate, 42.5 g of α-methylstyrene dimer, 120 g of azobisisoheptonitrile, and 2850 g of diethylene glycol methyl ethyl ether were added to a 5 L three-necked flask, and the temperature was raised to 70° C. with stirring, and the reaction was carried out for 4 h. The temperature was then lowered to room temperature to obtain an acrylic resin with Mw=8828, PDI=2.0, solid content of 27.35%, and viscosity of 19.03 cP.
[0038] Example 4 This example provides a synthesis of acrylic resin R-3 Under nitrogen protection, 130 g of the compound represented by formula (I), 137.5 g of methacrylic acid, 359 g of tetrahydrofurfuryl methacrylate, 205 g of 3,4-epoxycyclohexyl methacrylate, 176 g of α-methylstyrene, 223 g of lauryl methacrylate, 42.5 g of α-methylstyrene dimer, 120 g of azobisisoheptylnitrile, and 2850 g of diethylene glycol diethyl ether were added into a 5 L three-necked flask, and the temperature was raised to 70° C. with stirring, and the reaction was carried out for 4 h. The temperature was then lowered to room temperature to obtain an acrylic resin with Mw=9000, PDI=2.3, solid content of 26.80%, and viscosity of 18.44 cP.
[0039] Example 5 This example provides a synthesis of acrylic resin R-4 Under nitrogen protection, 95 g of the compound represented by formula (I), 137.5 g of acrylic acid, 310 g of glycidyl methacrylate, 182 g of tetrahydrofurfuryl methacrylate, 165 g of α-methylstyrene, 88 g of methyl methacrylate, 42.5 g of α-methylstyrene dimer, 120 g of azobisisobutyronitrile, and 2850 g of diethylene glycol methyl ethyl ether were added into a 5 L three-necked flask, and the temperature was raised to 70° C. with stirring, and the reaction was carried out for 4 h. The temperature was then lowered to room temperature to obtain an acrylic resin with Mw=9714, PDI=2.47, solid content of 27.15%, and viscosity of 19.33 cP.
[0040] Comparative Example This example provides the synthesis of acrylic resin R-5 (prepared without Compound I resin).
[0041] Under nitrogen protection, 137.5 g of methacrylic acid, 375 g of glycidyl methacrylate, 232 g of tetrahydrofurfuryl methacrylate, 155 g of α-methylstyrene, 88 g of methyl methacrylate, 42.5 g of α-methylstyrene dimer, 120 g of azobisisoheptonitrile, and 2850 g of diethylene glycol methyl ethyl ether were added into a 5L three-necked flask, the temperature was raised to 70°C with stirring, the reaction was carried out for 4 hours, and the temperature was lowered to room temperature to obtain an acrylic resin with Mw=10498, PDI=2.6, solid content of 28.42%, and viscosity of 19.56 cP.
[0042] Figure 4 This is the GPC chart of acrylic resin R-1 prepared in Example 2. Figure 5 This is the GPC chart of acrylic resin R-2 prepared in Example 3. Figure 6 This is the GPC chart of acrylic resin R-3 prepared in Example 4. Figure 7 This is the GPC chart of acrylic resin R-4 prepared in Example 5. Figure 8 This is the GPC chart of acrylic resin R-5 prepared as a comparative example. Fig. 9 This is a test chart of film adhesion (cross-hatch method). Fig.10 This is the outgas (TGA) diagram.
[0043] Depend on Figure 4~Figure 8 It can be seen that the GPC graph shows the molecular weight of the synthesized resin. Its molecular weight Mn, Mw and molecular weight distribution PD are consistent with the molecular weight distribution range of photoresist resins in current literature and related reports. There are no mandatory requirements in the specific implementation of photoresist resins. GPC is only a characterization parameter of the synthesized resin, indicating that the obtained product is a polymer compound and the molecular weight meets the expected requirements.
[0044] Fig. 9 The adhesion of the film after formation is tested by the cross-cut method, referring to the national standard GB / T 9286-2021. Fig. 9 It can be seen that the inner film surface of the squares formed after scribing is intact and has not fallen off, indicating that there is good adhesion between the film and the substrate.
[0045] Fig.10 : Outgas is used to measure the thermal stability of the material after film formation. The TG method test generally requires a weight loss of less than 5%. It can be seen from the figure that when the temperature reaches 230°C (the temperature required by the production line), the material still has 99.64% residual volume, indicating that the material has good thermal stability and meets the use requirements.
[0046] Example 6 This example provides a planarization layer composition for comparison with the comparative example.
[0047] Planarization layer composition 1: Under nitrogen protection, 15 g of glycidyl methacrylate, 18.5 g of hydroxyethyl methacrylate, 15 g of 4-isopropenylphenol, 10 g of benzyl methacrylate, 10 g of pentaerythritol triacrylate, 8.5 g of Irgacure® OXE01, 1.0 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-1 were added to a 5L three-necked flask in sequence, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter to obtain a planarization layer composition 1.
[0048] After the above composition is coated into a film, it is irradiated with UV light (igh mixed line) for 5 to 10 minutes, and then cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0049] Planarization layer composition 2: Under nitrogen protection, 15 g of glycidyl methacrylate, 18.5 g of hydroxyethyl methacrylate, 15 g of 4-vinylphenol, 15 g of phenoxyethyl methacrylate, 10 g of ethylene glycol methacrylate, 5.5 g of Irgacure® OXE01, 10 g of benzoyl peroxide, 1.0 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-2 were added to a 5L three-necked flask in sequence, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter to obtain a planarization layer composition 2.
[0050] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0051] Planarization layer composition 3: Under nitrogen protection, 20 g of glycidyl methacrylate, 10.5 g of hydroxyethyl methacrylate, 10 g of dicyclopentyl methacrylate, 10 g of 4-isopropenylphenol, 15 g of phenoxyethyl methacrylate, 10 g of ethylene glycol methacrylate, 4.5 g of Irgacure® OXE01, 5.5 g of 2,2-dimethoxy-phenyl acetophenone, 1.0 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-3 were added to a 5L three-necked flask in sequence, and the mixture was stirred for 4 h, and filtered through a 0.22 μm PTFE filter to obtain a planarization layer composition 3.
[0052] After the above composition is coated into a film, it is irradiated with UV light (igh mixed line) for 5 to 10 minutes and cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0053] Planarization layer composition 4: Under nitrogen protection, 15 g of glycidyl methacrylate, 18.5 g of hydroxyethyl methacrylate, 15 g of 4-vinylphenol, 15 g of benzyl methacrylate, 10 g of ethylene glycol methacrylate, 5.5 g of Irgacure®OXE01, 10 g of benzoyl peroxide, 1.0 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-4 were added sequentially into a 5L three-necked flask, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter membrane to obtain a planarization layer composition 4.
[0054] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0055] Planarization layer composition 5: Under nitrogen protection, 10 g of glycidyl methacrylate, 18.5 g of hydroxybutyl methacrylate, 15 g of 4-vinylphenol, 23 g of benzyl methacrylate, 10 g of ethylene glycol methacrylate, 5.0 g of Irgacure®OXE01, 10 g of benzoyl peroxide, 1.0 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-4 were added in sequence to a 5 L three-necked flask, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter membrane to obtain a planarization layer composition 5.
[0056] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0057] Planarization layer composition 6: Under nitrogen protection, 10 g of glycidyl methacrylate, 18.5 g of hydroxyethyl methacrylate, 15 g of 4-vinylphenol, 23 g of phenoxyethyl methacrylate, 10 g of ethylene glycol methacrylate, 6.4 g of Irgacure® OXE02, 10 g of benzoyl peroxide, 0.8 g of antioxidant 1076, 1.0 g of KP-340, 4.0 g of KH-570, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-1 were added to a 5L three-necked flask in sequence, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter to obtain a planarization layer composition 6.
[0058] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0059] Planarization layer composition 7: Under nitrogen protection, 8 g of glycidyl methacrylate, 20.5 g of hydroxypropyl methacrylate, 10 g of 4-vinylphenol, 5 g of 4-tert-butoxystyrene, 22 g of benzyl methacrylate, 5 g of ethylene glycol methacrylate, 8 g of pentaerythritol triacrylate, 7.8 g of Irgacure® OXE02, 8 g of benzoyl peroxide, 0.8 g of antioxidant 1076, 1.0 g of KP-341, 4.0 g of KH-560, 2250 g of propylene glycol methyl ether acetate, 280 g of propylene glycol monomethyl ether, and 305 g of acrylic resin R-3 were added to a 5L three-necked flask in sequence, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter to obtain a planarization layer composition 7.
[0060] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0061] Planarization layer composition 8: Under nitrogen protection, 7.5 g of tetrahydrofurfuryl methacrylate, 20.5 g of hydroxyethyl methacrylate, 10 g of 4-vinylphenol, 5 g of styrene, 20 g of benzyl methacrylate, 3 g of diethylene glycol methacrylate, 8 g of trimethylolpropane triacrylate, 5.5 g of Irgacure® OXE02, 8 g of benzoyl peroxide, 0.8 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 295 g of acrylic resin R-4 were added in sequence to a 5L three-necked flask, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter to obtain a planarization layer composition 8.
[0062] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0063] Planarization layer composition 9 (comparative example forming composition): Under nitrogen protection, 14 g of glycidyl methacrylate, 14.5 g of hydroxybutyl methacrylate, 13.5 g of 4-vinylphenol, 30 g of benzyl methacrylate, 12 g of ethylene glycol methacrylate, 6.5 g of Irgacure® OXE01, 8 g of benzoyl peroxide, 1.0 g of antioxidant 1010, 1.0 g of KP-341, 4.0 g of KH-560, 2450 g of propylene glycol methyl ether acetate, and 285 g of acrylic resin R-5 were added sequentially into a 5L three-necked flask, and the mixture was stirred for 4 h. The mixture was filtered through a 0.22 μm PTFE filter membrane to obtain a planarization layer composition 6.
[0064] After the above composition is coated to form a film, it is cured at a temperature of 150° C. to 250° C. for 5 to 15 minutes to complete the curing and obtain a flat layer material.
[0065] The comparison results of the planarization layer composition prepared in the above example and the comparative example are shown in Table 1.
[0066] Table 1: Performance comparison results
[0067] The planarization layer compositions (compositions 1 to 8) prepared by the present invention show comparable or better performance than existing materials in a number of key performance indicators. Specifically, they have a low density, which helps to reduce the weight of the overall device; a low dielectric constant, which helps to reduce delays and energy losses in signal transmission; extremely low water absorption, showing excellent moisture resistance; and high volume resistivity, ensuring good electrical insulation. In terms of physical and chemical stability, all compositions showed no precipitation and good stability in the Shock test and the Bubble test, and the Outgas (TGA) test also showed low volatility, moderate hardness and low film surface roughness, which is beneficial to subsequent graphics production and lithography processes. In addition, the composition exhibits high transmittance and little effect on optical properties; it passes both VCD Mura and Pin Mura tests, indicating good pattern uniformity and defect-free performance; it has strong adhesion and no peeling, ensuring a firm bond with the substrate; in terms of drug resistance, it has good tolerance to common solvents such as IPA, NMP, TMAH and DIW, and the film reduction is within an acceptable range, showing excellent chemical stability. In contrast, although the existing materials also perform well in most indicators, there is a small amount of peeling in the adhesion test and the transmittance is slightly lower, which indicates that the prepared composition has more advantages in flat layer applications.
[0068] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of preferred implementations of the present invention, and the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A compound, characterized in that Having a structure as shown in formula (I), 。 2. An acrylic resin, characterized in that The monomers constituting the acrylic resin include the compound according to claim 1, acrylic compounds, acrylate compounds, styrene compounds, and epoxy compounds.
3. The acrylic resin according to claim 2, characterized in that The acrylic compound is selected from at least one of acrylic acid and methacrylic acid; The acrylic acid ester compound is selected from at least one of methyl methacrylate, methacrylate, butyl methacrylate, tert-butyl methacrylate, lauryl methacrylate, decyl methacrylate, isobornyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, hydroxyethyl methacrylate, adamantyl methacrylate, dicyclopentyl methacrylate, and perfluorobutyl methacrylate; The styrene compound is selected from at least one of styrene, α-methylstyrene, 4-hydroxystyrene, 4-tert-butoxystyrene, 4-boc-styrene, p-divinylbenzene and 4-isopropenylphenol; The epoxy compound is selected from at least one of glycidyl methacrylate, tetrahydrofurfuryl methacrylate, and 3,4-epoxycyclohexyl methacrylate.
4. The acrylic resin according to claim 2, characterized in that The acrylic resin is formed by polymerizing the constituent monomers in a first solvent; The first solvent is selected from at least one of diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, methyl lactate, ethyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
5. The acrylic resin according to any one of claims 2 to 4, characterized in that The acrylic resin has a molecular weight of 3000-10000 Mw, a PDI of 2.0-3.0, and a solid content of 25%-35%.
6. A planarization layer composition comprising an acrylic resin, characterized in that: The acrylic resin is the acrylic resin according to any one of claims 2 to 5.
7. The planarization layer composition according to claim 6, characterized in that: The acrylic resin accounts for 1-30 wt % in the planarization layer composition.
8. The planarization layer composition according to claim 7, characterized in that: The planarization layer composition is composed of the following components in parts by mass: 10 to 300 parts of the acrylic resin; 10~300 parts of active diluent; 1~10 parts of photoinitiator and / or thermal initiator; 5~20 parts of coupling agent; 1~10 parts of surfactant; 1~10 parts of antioxidant; 10-80 parts of the second solvent.
9. The planarization layer composition according to claim 8, characterized in that: The active diluent is selected from at least one of glycidyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, hydroxyethyl methacrylate and styrene; The photoinitiator is selected from at least one of Irgacure® OXE01, Irgacure® OXE02, IRGACURE® 819, Irgacure® 290, benzophenone, diphenylacetophenone, and 2,2-dimethoxy-phenylacetophenone; The thermal initiator is at least one selected from benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate; The coupling agent is selected from at least one of divinylbenzene, 3,4-epoxycyclohexyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, KH-560, and KH-570; The surfactant is selected from at least one of TritonX-100, OP-10, polyoxyethylene sorbitan fatty acid ester, sulfobetaine, lecithin, KP-341, KP-420, KP-611, BYK-301, BYK-310, and BYK-3450; The antioxidant is selected from at least one of antioxidant 330, antioxidant 1010, antioxidant 1076, and antioxidant 3114; The second solvent is selected from at least one of diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, methyl lactate, ethyl lactate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and N-ethylpyrrolidone.
10. Use of the compound according to claim 1, or the acrylic resin according to any one of claims 2 to 5, or the planarization layer composition according to any one of claims 6 to 9 in a thin film transistor liquid crystal display, wherein the thin film transistor liquid crystal display is coated with a planarization layer, characterized in that: At least one of the flatness, adhesion, dielectric properties and tolerance is improved.
Citation Information
Patent Citations
Flat-layer composition, preparation method thereof, flat-layer material and display device
CN109422987A
Ink-jet printing ink composition, ink-jet printing ink, and ink-jet direct plate-making plate material
CN117467303A
Chemically amplified positive photosensitive planarizing film resin composition and insulating film
CN118169967A